Pelatihan Penggunaan Aplikasi Pilar-Pilar Sosial Berbasis Website Pada Dinas Sosial DKI Jakarta - Mufti; Nurwati; Yudi Santoso; Wahyu Pramusinto (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This training on the use of the social pillars application is one of the applications used by the Social Service in monitoring, fostering and evaluating the pillars accommodated by the Social Service. The purpose of this training is so that all pillar activities can be recorded and when you need the data, you can immediately display it with the latest data. The Social Service as a government agency has a big share in the welfare of the community through these pillars. This website-based social pillars application is expected to be a medium between the Social Service and the pillars. The training material provided contains how to use the application and its features, using a browser, logging into the application, inputting pillar registration, inputting pillar activities, displaying pillar activity reports and logging out of the application. The evaluation results of this training were 88% of the training participants were able to understand the training material on the use of the social pillars application and followed the training well, especially displaying pillar activity reports at 86%.